Interactions between ALDH2 rs671 polymorphism and lifestyle behaviors on coronary artery disease risk in a Chinese Han population with dyslipidemia: A guide to targeted heart health management - Liu Huang; Xiao Cai; Fuzhi Lian; Long Zhang; Yuling Kong; Chengjian Cao; Haiyan Ma; Yuxian Shao; Yinyin Wu; Baodan Zhang; Liangwen Xu; Lei Yang (Komiyama Printing Co. Ltd, 2018)
Abstract Background Both aldehyde dehydrogenase 2 (ALDH2) rs671 polymorphism and lifestyle behaviors are involved in coronary artery disease (CAD), while the interaction between them is currently unknown. Methods A nested case-control study was conducted in 161 patients with CAD and 495 controls in dyslipidemia population in Yinzhou District, Ningbo, Zhejiang Province, China, in August 2013. Anthropometric data and blood samples were collected, demographic characteristics and lifestyle behaviors information were obtained by a face-to-face interview, dietary intake was assessed by a food frequency questionnaire, and genomic DNA was genotyped. Results Carriers with increasing number of A alleles had an elevated CAD risk compared with G allele carriers (adjusted OR = 1.483, 95% CI = 1.114-1.974). Carriers of rs671 A/G and A/A genotypes had a higher CAD risk than carriers of G/G genotype (adjusted OR = 1.492, 95% CI = 1.036-2.148). Similarly, individuals with rs671 A/A genotype had a higher CAD risk than individuals with A/G and G/G genotypes (adjusted OR = 2.161, 95% CI = 1.139-4.101). We found a borderline additive interaction between regular fried food intake and A/A and A/G genotypes, and a significantly additive interaction between sedentary/light physical activity and A/A and A/G genotypes. Conclusions Individuals with A/A or A/G genotypes of rs671 have a higher CAD risk, if they lack physical activity and take fried food regularly, than individuals with G/G genotypes. These findings can help to provide a guide to targeted heart health management.